Pengaruh Pola Asuh Orang Tua Terhadap Pembentukan Karakter Anak - Sofi Kamilatus Sa’diah; Rania Roka; Ai Siti Nuratilah; Dede Wahyudin; Jennyta Caturiasari (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This study aims to describe the influence of parenting styles on the formation of children's character based on the results of a literature study. In this study a descriptive method was used using a qualitative approach and data collection techniques using literature studies from national journals and other internet sources relevant to the research topic. The results of the study show that parenting style has a very important influence on the development of children's character. The type of parenting that parents do for children will form different characters in developing the child's potential. Some types of parenting styles include authoritarian parenting, democratic parenting, and permissive parenting.